Avatāras, Goddesses, and Kauravas: Reading the Old Kannada Sauptikaparvan as an Alternative Ending to the Mahābhārata. (30th June 2021) - Lorndale, Timothy
Abstract: This article focuses on the reception history of the Sauptikaparvan in Old Kannada, examining two particular tellings of the Mahābhārata: the Vikramārjunavijaya of Pampa (VAV; ca. 941 C.E.) and the Sāhasabhīmavijaya of Ranna (SBhV; ca. 997–1008 C.E.). I argue that these two Old Kannada Mahābhāratas transform the Sauptikaparvan's iconic massacre into an episode about challenging the actions of Kṛṣṇa, the avatāra of Viṣṇu, and temporarily restoring Duryodhana to power. In doing so, the Kaurava king is allowed to end the war on his own terms. He ultimately dies upholding the principles of Kṣatriyadharma that he previously advocated and fought for. Through a close and comparative reading, I show how for these two texts the Sauptikaparvan becomes a space in which they can question and respond to larger issues of theology, dharma, and human effort in the Mahābhārata's reception history.